Clinical Applications Of Bone Allografts And Substitutes : Biology And Clinical Applications. - Phillips, Glyn O. (World Scientific, 2005)
Although bone allografts were first utilized by McEwen in orthopaedic surgery in 1881, progress since then has been sporadic. With the growth of tissue banks and the greater availability of safe and sterile bone grafts, the pace has now quickened; in 2004, more than one million such grafts were used in the USA alone. However, the practice generally remained a "cottage industry" well into the latter part of the 20th century. This volume provides an international expert evaluaton of the current use of bone, bone substitutes and related allografts, and describes up-to-date practices and clinical.